Incidence and outcome of colorectal cancer in liver transplant recipients: A national, multicentre analysis on 8115 patients. (9th November 2018) - Rompianesi, Gianluca; Ravikumar, Reena; Jose, Sophie; Allison, Michael; Athale, Anuja; Creamer, Felicity; Gunson, Bridget; Manas, Derek; Monaco, Andrea; Mirza, Darius; Owen, Nicola; Roberts, Keith; et al.
Abstract: Background & Aims: De novo malignancies after liver transplantation represent one of the leading causes of death in the long‐term. It remains unclear whether liver transplant recipients have an increased risk of colorectal cancer and whether this negatively impacts on survival, particularly in those patients affected by primary sclerosing cholangitis and ulcerative colitis. Methods: In this national multicentre cohort retrospective study, the incidence of colorectal cancer in 8115 evaluable adult patients undergoing a liver transplantation between 1 January 1990 and 31 December 2010 was compared to the incidence in the general population through standardised incidence ratios. Results: Fifty‐two (0.6%) cases of colorectal cancer were identified at a median of 5.6 years postliver transplantation, predominantly grade 2 (76.9%) and stage T3 (50%) at diagnosis. The incidence rate of colorectal cancer in the whole liver transplant population was similar to the general UK population (SIR: 0.92), but significantly higher (SIR: 7.0) in the group of patients affected by primary sclerosing cholangitis/ulcerative colitis. One‐, five‐ and ten‐year survival rates from colorectal cancer diagnosis were 71%, 48% and 31%, respectively, and the majority of colorectal cancer patients died of cancer‐specific causes. Conclusions: Liver transplantation alone is not associated with an increased risk of colorectal cancer development. The primary sclerosing cholangitis/ulcerative colitis liver transplant population showed a significantly higher risk of colorectal cancer development than the general population, with a high proportion of advanced stage at diagnosis and a reduced patient survival.